2018
DOI: 10.3389/fpls.2018.00582
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Vegetation Distribution in the East Dongting Lake After the Operation of the Three Gorges Dam, China

Abstract: Water regime is regarded as the primary factor influencing the vegetation distribution in natural wetland ecosystems. However, the effect of water regime change induced by large-scale hydraulic engineering on vegetation distribution is still unclear. In this study, multi-temporal TM/ETM+/OLI images and hydrological data from 1995 to 2015 were used to elucidate how the change in water regime influenced the vegetation distribution in the East Dongting Lake (EDTL), especially after the operation of the Three Gorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…We think this phenomenon can be attributed primarily to the higher adaptability of wetland vegetation to AID than its adaptability to IDU. For example, the study by Hu et al (2018) in the Dongting Lake wetland revealed that the distribution elevations of wetland vegetation varied to some extent in different years, although their annual inundation duration was relatively constant. It also indicated that IDU may be a better indicator to predict changes in vegetation production in response to wetland flooding patterns.…”
Section: Discussionmentioning
confidence: 99%
“…We think this phenomenon can be attributed primarily to the higher adaptability of wetland vegetation to AID than its adaptability to IDU. For example, the study by Hu et al (2018) in the Dongting Lake wetland revealed that the distribution elevations of wetland vegetation varied to some extent in different years, although their annual inundation duration was relatively constant. It also indicated that IDU may be a better indicator to predict changes in vegetation production in response to wetland flooding patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a single time series feature with the highest contribution was used for the classification for deriving the desired classes. This identification step is performed automatically by Since the TFV type is high grassland and reed (Figure 5b) [64], which is similar to the structure of some crops (rice, wheat), it is assumed that the vegetation can be penetrated by the C-band data [10,65]. Therefore, it is expected that the increase in backscatter values will occur at the time of the flood in the VV polarization due to their sensitivity to the double impact effect.…”
Section: Southernmentioning
confidence: 99%
“…Peng et al (2005) reported that the organic carbon density in Dongting Lake wetland soil at 1 m depth was 127.3 ± 36.1 t hm −2 , and the carbon density in the 0-30 cm topsoil was 46.5 ± 19.7 t hm −2 . Carex brevicuspis is a dominant species in the Dongting Lake wetland and has large carbon reserves (∼ 6.5 × 10 6 t yr −1 ) (Kang et al, 2009). However, due to the dam construction upstream of Dongting Lake, the water regime has varied considerably (early water withdrawal and decline of groundwater in non-flood season) in recent years, leading to a significant carbon loss in this floodplain wetland (Hu et al, 2018;Deng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%